In-vivo confirmation of the use of the dart thrower's motion during activities of daily living. (May 2014) - Brigstocke, G.H.O.; Hearnden, A.; Holt, C.; Whatling, G.
The dart thrower's motion is a wrist rotation along an oblique plane from radial extension to ulnar flexion. We report an in-vivo study to confirm the use of the dart thrower's motion during activities of daily living. Global wrist motion in ten volunteers was recorded using a three-dimensional optoelectronic motion capture system, in which digital infra-red cameras track the movement of retro-reflective marker clusters. Global wrist motion has been approximated to the dart thrower's motion when hammering a nail, throwing a ball, drinking from a glass, pouring from a jug and twisting the lid of a jar, but not when combing hair or manipulating buttons. The dart thrower's motion is the plane of global wrist motion used during most activities of daily living. Arthrodesis of the radiocarpal joint instead of the midcarpal joint will allow better wrist function during most activities of daily living by preserving the dart thrower's motion.